2021
DOI: 10.48550/arxiv.2105.12604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pro-étale uniformisation of abelian varieties

Abstract: For an abelian variety A over an algebraically closed non-archimedean field K of residue characteristic p, we show that the isomorphism class of the pro-étale perfectoid cover A = lim ← −[p]A is locally constant as A varies p-adically in the moduli space. This gives rise to a pro-étale uniformisation of abelian varieties as diamondsthat works uniformly for all A without any assumptions on the reduction of A.More generally, we determine all morphisms between pro-finite-étale covers of abeloid varieties. For exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…is the limit over multiplication by n on X, where n ranges through N. This is represented by a perfectoid space [6, Corollary 5.9] with the interesting feature that it is 'p-adic locally constant in X', that is, many different X have isomorphic 𝑋 [22]. 3.…”
Section: 𝑋 mentioning
confidence: 99%
“…is the limit over multiplication by n on X, where n ranges through N. This is represented by a perfectoid space [6, Corollary 5.9] with the interesting feature that it is 'p-adic locally constant in X', that is, many different X have isomorphic 𝑋 [22]. 3.…”
Section: 𝑋 mentioning
confidence: 99%
“…Proof Let V be finite free over Z p , then we consider the long exact sequence of Hom(−, V ) applied to the displayed sequence: Since V is derived p-complete and A p is p-divisible, we have by [21,Lemma A.10] Ext v ( A p , V ) = 0.…”
Section: Universal Z P -Extensionsmentioning
confidence: 99%
“…This gives an independent proof that a unipotent v-vector bundle is analytic if and only if its associated T p A-representation is trivial on T p C. Remark 4. 21 One way in which this perspective could be helpful is that in contrast to the approach via universal vector extensions, it does not use the group structure on A in an essential way. In particular, we believe that diamantine covers like A c can also help understand when generalised representations are representations beyond the case of abeloids.…”
Section: The Case Of Ordinary Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 5.3. In [10], it is shown that this is a "uniformisation" also in the stronger sense that for two abelian varieties A and A ′ , the perfectoid covers A ∞ and A ′ ∞ are isomorphic whenever A and A ′ are "p-adically close" in some precise sense. In particular, at least locally in the moduli space of abelian varieties we can really think of T p A as a 2d-dimension Z p -sublattice of a fixed perfectoid space determining A, in analogy to the complex uniformisation of abelian varieties.…”
Section: Uniformisationmentioning
confidence: 99%